Budesonide-loaded solid lipid nanoparticles for pulmonary delivery: preparation, optimization, and aerodynamic behavior. (16th November 2016) - Esmaeili, Maryam; Aghajani, Mahdi; Abbasalipourkabir, Roghayeh; Amani, Amir
Abstract: Advantages of lipid nanoparticles for pulmonary applications are possibility of deep lung deposition with prolonged release and low toxicity. This study aimed to evaluate the effects of formulation and processing parameters on particle size of prepared SLNs. Budesonide-loaded solid lipid nanoparticles (BUD-SLNs) were prepared with different values of drug content, ultrasonication amplitude, and homogenization time and the data were modeled using artificial neural networks (ANNs). Optimal conditions for fabrication of small-sized particles of 170–200 nm were found to be low drug content with high-amplitude and high-homogenization time. In vitro aerosolization performance of BUD-SLNs was then compared to that of commercial budesonide which indicated enhancement in fine particle fraction value.